Perceptions of Educated Women Through the Lens of the Intellectual Class - Iqbal Kazim Issa (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The mental image held by society’s educated class plays a pivotal role in shaping perceptions of women, especially in transitional democracies. Specific Background: In Iraq, where historical, cultural, and political contexts intersect, the representation of educated women remains complex and often contradictory. Knowledge Gap: Despite their increasing visibility, there is a lack of analytical studies that explore how the educated elite perceive their female counterparts. Aim: This research investigates the mental image of the educated Iraqi woman as perceived by the educated class, focusing on her electoral role, professional competence, cultural awareness, and concept of freedom. Results: The study reveals a nuanced perception—educated women are largely viewed as intellectually capable and socially resilient, yet still challenged by prevailing stereotypes and traditional norms. Novelty: By employing a descriptive-analytical method and drawing from literary and media representations, this study offers a multidimensional analysis rarely addressed in prior Iraqi scholarship. Implications: These findings provide insight for media, policymakers, and educators seeking to reform public narratives and support the advancement of women's roles in intellectual and civic life. Highlights: Highlights how educated elites shape perceptions of women in Iraq. Explores media and literature's role in constructing gendered images. Offers insights for policy and narrative reform in transitional societies. Keywords: Educated Women, Mental Image, Iraqi Intellectuals, Gender Representation, Media Influence